Novel and Conserved miRNAs Among Brazilian Pine and Other Gymnosperms - Galdino, José Henrique; Eguiluz, Maria; Guzman, Frank; Margis, Rogerio (Frontiers in Genetics, 2019)
The knowledge about plant miRNAs has increased exponentially, with thousands of miRNAs been reported in different plant taxa using high throughput sequencing technologies and bioinformatic tools. Nevertheless, several groups of plants remain unexplored, and the gap of knowledge about conifer miRNAs is considerable. There is no sequence or functional information available on miRNAs in Araucariaceae. This group is represented in Brazil by only one species, Araucaria angustifolia, an endangered species known as Brazilian pine. In the present study, Brazilian pine has its transcriptome explored with respect to small RNAs, representing the first description in a member of the Araucariaceae family. The screening for conserved miRNAs in Brazilian pine revealed 115 sequences of 30 miRNA families. A total of 106 precursors sequences were predicted. 41 comprised conserved miRNAs from 16 families, whereas 65 were annotated as novel miRNAs. The comparison of Brazilian pine precursors with sRNA libraries of other five conifer species indicates that 9 out 65 novel miRNAs are conserved among gymnosperms, while 56 seems to be specific for Brazilian pine or restricted to Araucariaceae family. Analysis comparing novel Brazilian pine miRNAs precursors and Araucaria cunninghamii RNA-seq data identified seven orthologs between both species. Mature miRNA identified by bioinformatics predictions were validated using stem-loop RT-qPCR assays. The expression pattern of conserved and novel miRNAs was analyzed in five different tissues of three-month-old Araucaria seedlings. The present study provides insights about the nature and composition of miRNAs in an Araucariaceae species, with valuable information on miRNAs diversity and conservation in this taxon.cunninghamii RNA-seq data identified seven orthologs between both species. Mature miRNA identified by bioinformatic predictions were validated using stem-loop RT-qPCR assays. The expression pattern of conserved and novel miRNAs was analyzed in five different tissues of three-month-old Araucaria seedlings. The present study provides insights about the nature and composition of miRNAs in an Araucariaceae species, with valuable information on miRNAs diversity and conservation in this taxon.